Dance and Stillness: A Phenomenological Hermeneutic Inquiry Into the Experience of Stillness: Presented Through the Medium of Dance Performance and Written Exegesis - De Leon, Jennifer (Auckland University of Technology, 2007)
This thesis explores the subject of stillness: specifically the stillness that occurs in the midst of movement, turbulence or chaos. It is found in the midst of movement and can also be conceived as that which frames, or holds all movement. A principal focus of the thesis is to distinguish the therapeutic value of this stillness.The research methodology is hermeneutic phenomenology. Within this framework a choreographed dance work and written exegesis comprise and are equal parts of the whole. The choreography for the dance work employs a neo-classical-contemporary technique particular to the choreographer. A story and a journey are presented - providing a vehicle for the central theme of the thesis - stillness within movement, to be best elucidated. A Christo-centric philosophy and worldview are ground of the work.The dance work is choreographed on and presented by four dancers. These four dancers and four 'watchers' are the research participants. As the dance work evolved it was presented 'in process' and the participants interviewed subsequent to the showings. These interviews were not psychotherapy sessions, so data about interventions, process and outcome does not appear. Rather information was sought about the essence of the danced / watched experience, with particular attention being given to the felt experience of stillness. Data gained from these interviews constitutes the findings of the research.The findings show that the particular stillness exampled in this dance work is therapeutic, and therapeutic experience for the individual participants was realised. The data suggests the stillness was experienced in a number of different ways.These include: a personal relationship with chaos, the significance of relationship with each other, the particular relevance of design and time in the individual's life, the meaning of authenticity, the relevance and meaningfulness of symbolism, and the personal understanding of awareness, focus and release.This research shows that we who are psychotherapy clients, practitioners, and people of all walks would greatly benefit through including into daily life this 'stillness immanent within movement.'
Keywords: Dance; Movement; Choreography; Design; Time; Stillness; Authenticity; Symbolism